School evaluation mechanism in BRAC education programme - Nath, Samir R (Research and Evaluation Division, Brac, 2019)
This paper aims to examine the existing school evaluation provision in BRAC non-formal primary education programme. Information for this paper, was collected through scanning of existing documents, and discussing with the programme personnel at various levels. The examination focuses the process of evaluating school quality considering school as a unit of analysis. It was observed that there is a school evaluation system in BRAC education programme. Although the system is not sound enough it serves the programme with some limitations. There is possibility that all attempts regarding school improvement are not reflected in the evaluation process. This paper also analyses the limitations in current practices and provides suggestions for improvements.